Preparation of Surface-Enhanced Raman Scattering Substrates Based on Immobilized Silver-Capped Nanoparticles. (8th April 2018) - Caro, C.; Gámez, F.; Zaderenko, A. P.
Abstract : Novel results concerning surface-enhanced Raman scattering mediated by thiol-immobilized capped silver nanoparticles attached to a silicon Si(100) substrate are presented. The attachment of the nanoparticles is achieved by chemically modifying the surface of Si(100) in order to provide sulfhydryl groups covalently linked to the substrate and then covering these surfaces with bare and polymer-capped silver nanoparticles. The modified silicon substrate, the nanoparticles, and the sensors are characterized by means of infrared and UV-vis spectroscopies and electronic microscopies. The surface-enhanced Raman scattering intensity of the new films based on polymer-capped nanoparticles is compared with that obtained with silver bare nanoparticles using rhodamine 6G as a common chromophore. These results open a new route to the design of reversible and spot-to-spot reproducible surface-enhanced Raman scattering-based sensors supported by silver nanoparticles.